The Correlation of Midwife Professionalism with Loyalty of IUD Family Planning Acceptors at Health Center Simpang Tiga Bukit District Bener Meriah Regency - Herna Rinayanti (Institute of Computer Science (IOCS), 2021)
Professionalism reflects a person's attitude towards his profession. Along with the increasing demand from the community for quality services, especially health services, local governments must strive to improve services in all aspects and fields, one of which is loyalty to the use of family planning acceptors. The purpose of this study was to examine the correlatioj between the professionalism of midwives and the loyalty of IUD family planning acceptors. Observational analytic research method with cross sectional design. The sample in this study amounted to 62 people. Data analysis using spearman rank. The results showed that most of the respondents chose the professionalism of the midwife as many as 42 respondents (67.74%) strong, Most of the respondents had high loyalty as many as 42 respondents (67.74%). The results of the Spearman Rank test p = 0.002, there is a relationship between professionalism and work loyalty of midwives. Therefore, it is expected that health workers at Simpang Tiga Health Center, District Hill District. Bener Meriah can always maintain the professionalism of the midwife and always maintain communication and work motivation with the midwife or other health workers.